ANALISIS PEMANFAATAN PELAYANAN KELUARGA BERENCANA PASCA PERSALINAN DI WILAYAH KERJA PUSKESMAS PADANGSARI - Manullang, Jessika Putri Natasya; Nandini, Nurhasmadiar; Budiyanti, Rani Tiyas (Jurnal Manajemen Kesehatan Indonesia, 2024)
Postpartum family planning is a contraceptive service targeting mothers who have just given birth 0-42 days with the aim of preventing unwanted pregnancies. The high maternal mortality rate is caused by complications during pregnancy, so it is very important to use postpartum contraception. However, in Puskesmas Padangsari working area, the utilization of postpartum family planning services was very low,namely 28,47%. Therefore, this research was conducted with the aim of analyzed the utilization of postpartum family planning services in the Puskesmas Padangsari working area.This research was a quantitative research with a cross sectional approach using the accidental sampling technique where from a population of 198 mothers giving birth from January to December 2023, the sample was calculated using the slovin formula and with an error degree of 7%, a minimum sample size of 101 respondents was obtained. The research was carried out form January to March 2024.Bivariate data analysis using logistic regression test. Based on the research results, 44,7% of respondents had poor utilization of postpartum family planning services. Factors that did not influence the use of postpartum family planning services are mistrust, perception,and communication between service providers and patients. Meanwhile, the factors that influence the utilization of postpartum family planning services are cultural competency (p=0,069), perceived need (p=0.001), and customer satisfaction (p=0.005).